If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -5) + 2 = 8(2x + 5) + -2x Reorder the terms: 4(-5 + x) + 2 = 8(2x + 5) + -2x (-5 * 4 + x * 4) + 2 = 8(2x + 5) + -2x (-20 + 4x) + 2 = 8(2x + 5) + -2x Reorder the terms: -20 + 2 + 4x = 8(2x + 5) + -2x Combine like terms: -20 + 2 = -18 -18 + 4x = 8(2x + 5) + -2x Reorder the terms: -18 + 4x = 8(5 + 2x) + -2x -18 + 4x = (5 * 8 + 2x * 8) + -2x -18 + 4x = (40 + 16x) + -2x Combine like terms: 16x + -2x = 14x -18 + 4x = 40 + 14x Solving -18 + 4x = 40 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -18 + 4x + -14x = 40 + 14x + -14x Combine like terms: 4x + -14x = -10x -18 + -10x = 40 + 14x + -14x Combine like terms: 14x + -14x = 0 -18 + -10x = 40 + 0 -18 + -10x = 40 Add '18' to each side of the equation. -18 + 18 + -10x = 40 + 18 Combine like terms: -18 + 18 = 0 0 + -10x = 40 + 18 -10x = 40 + 18 Combine like terms: 40 + 18 = 58 -10x = 58 Divide each side by '-10'. x = -5.8 Simplifying x = -5.8
| 8r+r=-18 | | 4(7x-1)+3(2.5x)-4(3x+5)=-6 | | 164-5x=40x+19 | | -x/11=10 | | 16x-4=9x | | x=18/(18/x) | | 9-10x=69-24x | | r/7=-1 | | 0=8-4*6p-5+1 | | 4y=2x-8 | | 0=8-46p-5+1 | | 7x(3x-10)=6+(x-9) | | 4q/3=6/7 | | 3/2-4 | | 2-0/12-4 | | 2-0/12-(-4) | | -4+48+1r=15 | | 89=5b-7(1-b) | | (9-3x)3=-10x+21 | | 27+9v=0 | | 4x-3=7x+13 | | 4a+3=8+29 | | 6(3v+3)+3=6v-27 | | -9(y+8)=-3y-30 | | 6x(x+3)= | | 7+2x+3y=62 | | 2x-3=10-3(4x-5) | | (X+17)(X-8)=21(X-8) | | 5v^2-60v+160= | | (2x+1)+(2x+3)+(2x+5)=105 | | 5y-4=y+20 | | 2r^2+22r+60= |